2020
DOI: 10.1007/s13205-019-2010-3
|View full text |Cite
|
Sign up to set email alerts
|

Micropropagation of Guarianthe skinneri (Bateman) Dressler et W. E. Higging in Temporary Immersion Systems

Abstract: This study's aim was to establish a protocol for the micropropagation of G. skinneri using temporary immersion system (TIS). Different concentrations of 6-Benzylaminopurine (0, 1, 2, and 3 mg L −1 ), three different systems of cultivate semi-solid (SS) and liquid media under partial (PI) and temporary immersion systems (TIS), different compositions of the inorganic salts, and the number of subcultures were evaluated. The results showed a maximum of 16.56 shoots per explant obtained through TIS, adjusting all t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In addition, no published reports are available on in vitro establishment and propagation of B. nodosa. Most recently, some studies have showed improved efficiency of orchid micropropagation in liquid culture (Young et al 2000;Leyva-Ovalle et al 2020). Liquid culture systems may offer some advantages over semi-solid media in in vitro systems improving plant growth and development and providing higher rates of multiplication and the potential of reduction in manipulation and labor costs via automation (Ziv 2000).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, no published reports are available on in vitro establishment and propagation of B. nodosa. Most recently, some studies have showed improved efficiency of orchid micropropagation in liquid culture (Young et al 2000;Leyva-Ovalle et al 2020). Liquid culture systems may offer some advantages over semi-solid media in in vitro systems improving plant growth and development and providing higher rates of multiplication and the potential of reduction in manipulation and labor costs via automation (Ziv 2000).…”
Section: Introductionmentioning
confidence: 99%
“…(Wu et al 2007), Guarianthe(Leyva-Ovalle et al 2020), and Cattleya (Ekmekçigil et al 2019). These results warrant further investigation on the potential of TIS bioreactors for the micropropagation of B. nodosa.…”
mentioning
confidence: 99%
“…Recently, several studies have shown that TIS have numerous advantages as regards the semi-solid methods (Vidal and Sánchez, 2019 ). These systems have been successfully used for micropropagation of Stevia rebaudiana (Melviana et al, 2021 ), Colocasia esculenta L. Schott (Mancilla-Álvarez et al, 2021 ), Agave angustifolia (Monja-Mio et al, 2021 ), Rosmarinus officinalis L. (Villegas-Sánchez et al, 2021 ), Dracocephalum forrestii (Weremczuk-Jezyna et al, 2020 ), Guarianthe skinneri (Leyva-Ovalle et al, 2020 ), and the number is increasing steadily. In our laboratory, we have developed protocols using bioreactor propagation systems with liquid medium for axillary shoots of chestnut, alder and willow (Vidal et al, 2015 ; Cuenca et al, 2017 ; Regueira et al, 2018 ; San José et al, 2020 ; Gago et al, 2021 ), and somatic embryos of Quercus robur (Mallón et al, 2012 , 2013 ).…”
Section: Introductionmentioning
confidence: 99%
“…Micropropagation offers an alternate solution for the production of a large number of plants within a short time (Leyva‐Ovalle, Bello‐Bello, Murguía‐González, Núñez‐Pastrana, & Ramírez‐Mosqueda, 2020). The ambient in vitro culture environment allows plants to grow in aseptic conditions with reduced light intensity, higher humidity, rich carbohydrate, nutrients, and growth regulators (Hazarika, 2003; Teixeira da Silva et al, 2015).…”
Section: Introductionmentioning
confidence: 99%